Smooth bilinear forms of L(^2R_h(w_1, w_2)^2) and L(^2R_h^’(w_1, w_2)^2) - Kim, S. G.; Lee, C. Y. (Methods of Functional Analysis and Topology, 2023)
We characterize smooth points of unit balls in some spaces of bilinear forms on R^2. We find that for some special cases of hexagonal norms, the set of smooth points of the unit ball of symmetric bilinear forms coincides with the set of those smooth points of the unit ball of bilinear forms that are symmetric. Надано характеристику гладким точкам одиничних куль в деяких просторах білінійних форм на R^2. Знайдено, що для деяких частинних випадків гексагональних норм множина гладких точок одиничної кулі співпадає з множиною тих гладких точок одиничної кулі білінійних форм, які є симетричними.